2007
DOI: 10.1002/pola.21908
|View full text |Cite
|
Sign up to set email alerts
|

Propylene polymerizations with a binary metallocene system—Chain shuttling caused by trimethylaluminium between active catalyst centers

Abstract: Propylene was polymerized at varying trimethylaluminium (TMA) concentration with a homogeneous binary metallocene catalyst system activated by methylaluminoxane (MAO) in an attempt to better understand interactions between active catalyst sites and to clarify the role of the TMA as a chain shuttling agent. TMA‐free polymerization conditions were obtained by chemical treatment of MAO solution with 2,6‐di‐tert‐butyl‐4‐methylphenol (BHT). A binary catalyst system consisting of catalyst precursors diphenylmethyl(c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…By applying this arithmetic calculation to the nine physical mixtures carried out, it can be concluded that the variation between calculated and experimental catalytic activity is 14.5 % on average. Nevertheless, this correlation does not hold for hybrid catalysts, because when hybrid catalysts are employed, the participation of each active center is random [12][13][14][15][16], so catalytic activity may change depending on the homogeneity in the hybrid catalyst when both metallocenes are anchored on the silica support. Thus, in this case the activities are considerably Kg PP/mol Zr·h·bar, which is closer to 2100 achieved by the hybrid catalyst.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…By applying this arithmetic calculation to the nine physical mixtures carried out, it can be concluded that the variation between calculated and experimental catalytic activity is 14.5 % on average. Nevertheless, this correlation does not hold for hybrid catalysts, because when hybrid catalysts are employed, the participation of each active center is random [12][13][14][15][16], so catalytic activity may change depending on the homogeneity in the hybrid catalyst when both metallocenes are anchored on the silica support. Thus, in this case the activities are considerably Kg PP/mol Zr·h·bar, which is closer to 2100 achieved by the hybrid catalyst.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, in this case the activities are considerably Kg PP/mol Zr·h·bar, which is closer to 2100 achieved by the hybrid catalyst. In comparison with individual catalysts, hybrid catalysts present a decrease of activity due to the interaction between both active catalytic centers [12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sterically hindered phenols 2,6-di-t Bu,4-Me-C 6 H 2 OH (BHT-H), 2,4,6-tri-t Bu-C 6 H 2 OH (BHT*-H), and methylaluminum diaryloxides ((BHT) 2 AlMe and (BHT*) 2 AlMe) are sometimes used as the component of catalyst system in olefin polymerization. Phenols are applied for binding of free trimethylaluminum (TMA) [7][8][9][10][11][12][13][14][15] containing in commercial MAO up to 30 mol % since TMA is capable of blocking the active sites. [16][17][18] Sterically hindered phenols are inert toward catalytic intermediates even at high excess to metallocene and cause no lowering of the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was demonstrated that adding of phenol to reaction medium enables to control the molecular weight and microstructure of derived (co)polymers. 11,12,14,15 Methylaluminum diaryoxides with tert-butyl substituents in ortho-positions of aryloxy groups simultaneously act as moisture impurities scavanger. 9,10 Several publications about application of phenols in order to obtain highly effective activators of metallocene complexes should be noted.…”
Section: Introductionmentioning
confidence: 99%